Malignant catarrhal fever. I. Response of American cattle to malignant catarrhal virus isolated in Kenya. - Kalunda, M (1981)
Fifty-three American cattle were inoculated with malignant catarrhal fever virus isolated from a wildebeest in Kenya. Three animals showed the mild form of the disease and recovered, and 47 showed the severe form of the disease. The other three did not react. Of the 47 cattle, 28 died, 16 were killed for the collection of specimens and three recovered. The incubation period for the 47 cattle ranged from 16 to 29 days and the course of the fatal disease for 28 cattle averaged three to 23 days. Virus titration of specimens from nine infected steers yielded a mean titer of 10(4)/TCID50 per gm for lymph nodes, 10(3) TCID50 per mL for buffy coats and 10(2.3) TCID50 per gm for spleens. Smaller amounts of virus were found in the liver, kidneys, adrenals and thyroids. Malignant catarrhal fever virus was also found in nasal secretions and saliva of viremic cattle. Viral infectivity was shown in bovine buffy coat cells stored at 4 degrees C for two days but was immediately destroyed upon freezing even when glycerine or dimethylsulfoxide was added. Viral particles were not found in infected animal tissues by electron microscopy. The disease was successfully transmitted in steers by intratracheal intubation and by aerosol inhalation but not by contact.